2013
DOI: 10.1007/s00429-013-0632-5
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular signal-regulated kinase1/2-dependent changes in tight junctions after ischemic preconditioning contributes to tolerance induction after ischemic stroke

Abstract: Less disruption of the blood-brain barrier (BBB) after severe ischemic stroke is one of the beneficial outcomes of ischemic preconditioning (IP). However, the effect of IP on tight junctions (TJs), which regulate paracellular permeability of the BBB, is not well understood. In the present study, we examined IP-induced changes in TJs before and after middle cerebral artery occlusion (MCAO) in mice, and the association between changes in TJs and tolerance to a subsequent insult. After IP, we found decreased leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…Second, the JNKs and third, p38, respond to different types of cellular stress and inflammatory mediators (50). Activation of ERK1/2 results in increased ZO-1 degradation during traumatic brain injury (51), decreased ZO-1 and claudin 5 expression in brain endothelium during HIV infection (52,53), and reduced occludin and claudin 5 expression in BBB endothelium during ischemic stroke (54). Whether Snail1 is similarly involved in tight junction disruption under these conditions remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the JNKs and third, p38, respond to different types of cellular stress and inflammatory mediators (50). Activation of ERK1/2 results in increased ZO-1 degradation during traumatic brain injury (51), decreased ZO-1 and claudin 5 expression in brain endothelium during HIV infection (52,53), and reduced occludin and claudin 5 expression in BBB endothelium during ischemic stroke (54). Whether Snail1 is similarly involved in tight junction disruption under these conditions remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…TJ transmembrane proteins, such as occludin and claudin-5 or Zo-1, play a key role in the functional preservation of the BBB (Bazzoni et al, 2000;Hawkins & Davis 2005). As astrocyte endfeet cover over 95% of the brain capillary surface, the swelling of astrocyte endfeet causes disassembly of the tight junction network and decreased expression of TJ proteins such as occludin and claudin-5 (Shin et al, 2015;Willis, Leach, Clarke, Nolan, & Ray, 2004). In this study, we observed extensive EB extravasation into brain parenchyma in the IL hemispheres of the control mouse brains, indicating vascular leakage.…”
Section: Astrocytic Nhe1 Protein In Microvessel Damage and Bbb Leakagementioning
confidence: 99%
“…A 5-point graded scoring system for neurological scores and the wire suspension test was used (Shin et al, 2015). Forelimb strength was measured with the Grip strength tester bio-GS3 (BIOSEB, Virtolles cedex, France) prior to and 3 days after MCAO.…”
Section: Behavioral Testsmentioning
confidence: 99%